Morphological tool to elucidate two closely related pangasius catfish - Fitri, Muhammad Yusof; Christanus, Annie (IIUM Press, 2020)
Analyses of conventional morphometric, meristic and truss morphometric were performed on two species of Pangasiid catfish, Pangasianodon hypophthalmus and P. nasutus. The purpose is to find characters that help in differentiating these two species to avoid confusion among fish farmers. Three morphometric approaches (conventional, meristic and truss morphometric) were employed to identify the morphological differences. Conventional morphometric suggested eye diameter, body width, body depth, dorsal fin base length and barbells as characters that have significant differences (P< 0.05) between the species, hence making them as potential diagnostic markers. Truss morphometric analyses approved that P. nasutus have larger dorsal fin base length as suggested by conventional morphometry data. Meristic analysis showed significant difference (P<0.05) in number of dorsal fin rays, pelvic fin rays, anal fin rays and caudal fin rays. All three types of morphometric prove to support in elucidating the two species.